Development of an app for processing data on wildlife density in the field. Issue 12 (2nd December 2022) - ,; Blanco‐Aguiar, JA; Acevedo, P; Apollonio, M; Carniato, D; Casaer, J; Ferroglio, E; Guerrasio, T; Gómez‐Molina, A; Jansen, P; Illanas, S; Laguna, E; et al.
Abstract: It is essential to provide tools to wildlife professionals and researchers in order to facilitate data collection on wildlife density estimation following standardized protocols in the field. This is relevant for efficient harmonized data management systems, from the field to final reporting. Our main objective was to facilitate the collection of information in the field using established density estimation protocols. The specific objectives were (i) to evaluate and use already existing data registration IT tools for collecting and storing the data in the field; (ii) to make these data available in real time (cloud‐based solution), and (iii) being flexible enough to incorporate new protocols and species, as methods (such as camera trap‐based) and needs continuously evolves. We improved an already existing tool, Spatial Monitoring and Reporting Tool (SMART; https://smartconservationtools.org/ ). It is an open source software, which allows easily collect, visualize, store, analyze, report and act on a wide range of field data relevant for wildlife monitoring. The integration of SMART tools on EOW was successfully done for (i) distance sampling, (ii) hunting data and (iii) camera trap protocols. ENETWILD, therefore, made now available new IT functionalities to wildlife professionals and researchers to facilitate and harmonize wildlife data collection systems.